LEGAL CERTAINTY IN THE PROTECTION OF WITNESSES AND VICTIMS OF GROSS HUMAN RIGHTS VIOLATIONS - Nanda Ivan Natsir (Jurnal IUS Kajian Hukum dan Keadilan, 2013)
Law certainty in the protection of witnesses and victims of major human rights violation. The human right is a right that every human posses by not view any difference on race, skin color, gender, language, religion, political or other opinion. The Human rights is legally covered by a Human rights law that perhaps keep individuals or group protect from actions violating basic freedom as well as dignity and prestige for human being. One of the of HR laws with existence is a Universal Declaration for Human Rights of 1948 enacted by the United Nations. For law enforcement on Human rights the Indonesian government also has another Human Rights law namely the Regulations NO. 39 of 1999 about Human Rights and the Regulations No. 26 of 2000 about Human rights Court. In addition, this Government also has already ratified some instruments of International Human rights such as a convention on Political Right of Women that ratified by the Regulations No. 68 of 1958.  Ratification is an official expression of a state for obeying without any pressure upon the content of agreement. On 17th July 1998, within a Diplomatic Conference of UN there was already resulted an important step in law enforcement for Human rights namely for agreeing Roman Statute means an agreement to establish an International Criminal Court with the intends to keep try the human criminal in action and cut off any chain on law immune. Out of 148 states of participant in conference took part and that time found at least 120 states support it, 7 to opposite and 21 abstain. There are four sorts found as a seriously violation act that regulated in Roman Statutes, they are: 1. Genocide 2. Evil on Human 3. War Evil 4. Aggression evil.   Since so many violation cases on Human right heavy on this country such as Aceh case, East Timor case, Trisakti case and so forth till today the process for completion not satisfied any more. According to Government reasonable point out for refusing to ratify the Roman Statute concerned the International Criminal Court seemly to undermine the government authority. Whereas the International Criminal Court has its complementary principle, namely the International court is only as complement for the national court system whenever our national court unable or wish no to try the suspected. In addition, if the Indonesian government may ratify the Roman Statute politically it shall give advantages for Indonesia since other see how seriously the Indonesian government to keep completion the problem of Human right violation. It is at last, the international conviction over the national court in Indonesia may get recovery according to their view.Keyword : Criminal Act, Criminal Policy